2020
DOI: 10.3389/fmicb.2020.588658
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Perturbations Caused by the Over-Expression of mcr-1 in Escherichia coli

Abstract: Rapid dissemination of the plasmid-born polymyxin resistance gene mcr-1 poses a critical medical challenge. MCR-1 expression is tightly controlled and imposes a fitness cost on the bacteria. We used growth studies and metabolomics to examine growth and metabolic changes within E. coli TOP10 at 8 and 24 h in response to different levels of expression of mcr-1 . Induction of mcr-1 greatly increased expression at 8 h and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Consistent with the results of the previous studies that overexpression of mcr-1 impairs viability ( 38 , 39 ), and that mcr-1 is generally found in low-copy plasmids ( 40 ), our results suggest that maintaining the mcr-1 plasmid at a low copy number is essential for the fitness of the host bacteria. Furthermore, PcnR maintains a balance between the mcr-1 expression level and bacterial fitness by reducing the copy number of the IncI2 plasmid pHNSHP45 to ensure appropriate expression levels of mcr-1 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the results of the previous studies that overexpression of mcr-1 impairs viability ( 38 , 39 ), and that mcr-1 is generally found in low-copy plasmids ( 40 ), our results suggest that maintaining the mcr-1 plasmid at a low copy number is essential for the fitness of the host bacteria. Furthermore, PcnR maintains a balance between the mcr-1 expression level and bacterial fitness by reducing the copy number of the IncI2 plasmid pHNSHP45 to ensure appropriate expression levels of mcr-1 .…”
Section: Resultssupporting
confidence: 92%
“…Although the acquisition of antimicrobial resistance by mutation or HGT is often associated with a fitness cost, bacterial evolution to reduce the cost of resistance contributes to the persistence of resistance in pathogens ( 6 ). High-level expression of mcr-1 has previously been shown to influence bacterial fitness by impairing the growth rate and membrane structural integrity of the host bacteria ( 38 , 39 ). It is likely that maintaining a modest expression level of mcr-1 by a low copy number plasmid plays a key role in the persistence of mcr-1 plasmids in bacterial populations.…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, we compared the growth rates of mcr-1 -positive and mcr-1 -negative strains with those of their relevant HLCR mutants and found that HLCR mutants derived from mcr-1 -negative strains exhibited almost no fitness cost, while HLCR mutants of mcr-1 -positive strains showed an evident fitness cost. Previous studies have shown that the fitness cost attributed to chromosomal mutations or the acquisition of wild-type mcr-1 -harboring plasmids seemed to be insignificant ( Cannatelli et al, 2015 ; Wu et al, 2018 ); however, increased expression of mcr-1 could impose a significant fitness burden on host bacteria ( Yang et al, 2017 ; Liu et al, 2020 ). Our results demonstrated that the coexistence of chromosomal mutations and mcr-1 was disadvantageous for K. pneumoniae , which might partly explain the lack of clinical strains with both chromosomal mutations and mcr-1 ( Nang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mcr genes confer polymyxin resistance by encoding a phosphoethanolamine (pEtN) transferase enzyme (e.g., MCR-1, an inner-membrane (IM)-anchored protein) that catalyzes the addition of pEtN onto a phosphate at the N -acetylglucosamine headgroup of lipid A in the outer membrane (OM; Figure a). , However, this modification usually comes at a cost to the bacterium with the growth rate of mcr-1 positive transformants often substantially lower than that of non-MCR parents. Additionally, changes in cellular morphology and global metabolic perturbations mainly involving disruption to the bacterial membrane have also been reported with mcr-1 expression. , These results indicate that the acquisition of mcr genes is a “poisoned chalice” for bacteria that protects them from polymyxins but simultaneously has a fitness cost. However, the mechanism(s) by which modification of lipid A with pEtN results in negative consequences for the bacterium are unknown.…”
mentioning
confidence: 99%
“…As the expression of mcr is known to induce morphological changes in bacteria, , the influence of different proportions (0–75%) of pEtN-modified lipid A (i.e., lipid A-pEtN) on the morphology of biomimetic bacterial OMs was first investigated. The different proportions of lipid A-pEtN represent different extents of mcr expression.…”
mentioning
confidence: 99%